Climate change, economic security, and macroeconomic stability: Insights from the EU - Lobonț Oana-Ramona; Vătavu Sorana; Nicolescu Ana-Cristina; Trip Andrei; Costea Florin (BIO Web of Conferences)
This research examines the impact of climate change risks on the macroeconomic situation and the security of the economic system in the EU-27 during the 2002-2020 period. By employing methodologies such as the Ordinary Least Squares and Principal Component Analysis, the study evaluates the interrelationship between Climate Change Risk (CCR), Macroeconomic Situation (MS), and Economic System Security (ESS). The research develops composite indicators to analyse these phenomena in detail, while results reveal significant variations in CCR, MS, and ESS among EU member states, indicating a heterogeneous response to climate risks and economic stability and highlighting the need for differentiated policy approaches. Our research contributes to understanding the impacts of climate change on economic structures by providing insights into policy formulation and strategic planning to strengthen economic resilience and emphasising the need for an interdisciplinary approach that connects climate variables with economic indicators. The strategic alignment at national levels supports global sustainability efforts and ensures a unified and effective response to climate risks within the European economic system.